Intrapartum-related adverse perinatal outcomes : burden, consequences, and models of care from studies in eastern Uganda - Phillip Wanduru (2025)
Introduction: Intrapartum-related complications are a major contributor to adverse perinatal outcomes, including stillbirths, neonatal deaths, and intrapartum-related neonatal encephalopathy (IP-NE). However, most existing research focuses on single outcomes, often missing the broader spectrum of birth-related complications. There is also limited cohort evidence on the long- term consequences for infants who survive with IP-NE, despite known risks of developmental disabilities. Furthermore, although parental involvement in the care of newborns correlates with improved outcomes, the practical implementation of strategies that promote parent-newborn closeness, especially in low-resource neonatal settings, remains insufficiently documented.The objective: This study aimed to determine the prevalence of intrapartum- related adverse perinatal outcomes, assess one-year outcomes for survivors, and explore the experiences and perceptions of mothers and healthcare providers regarding parental participation in the care of critically ill newborns.Methods: The study was conducted at two hospitals in Eastern-Central Uganda. Sub-study 1 was a cross-sectional study with a nested case-control design, examining the births of babies weighing over 2,000 grams between June and December 2022. Data from a prospective perinatal registry were used to estimate the prevalence of intrapartum-related adverse outcomes, including stillbirths, neonatal deaths within 24 hours, and IP-NE, which was defined using an Apgar score 5.5 mmol/L, and a Thompson score of >5. Sub-study 2 followed infants diagnosed with IP-NE for one year and compared their survival outcomes to healthy newborns using the life table method. Sub-studies 3 and 4 were exploratory qualitative studies involving 18 in- depth interviews with mothers and 16 interviews with healthcare providers in neonatal units. These interviews were audio-recorded, transcribed, and analysed using reflexive thematic analysis.Results: Among 6,550 births, 10.2% resulted in adverse perinatal outcomes, including 3.8% stillbirths, 0.6% neonatal deaths, and 5.7% instances of IP-NE. Emergency referrals and caesarean sections did not alter the relationship between IP-NE and obstetric risk, except in cases of prolonged or obstructed labour. At the 12-month follow-up, healthy and mild IP-NE neonates displayed relatively high cumulative survival rates, each exceeding 95%. Neonates with moderate IP-NE experienced a lower survival rate of 87%. Notably, those with severe IP-NE faced the poorest outcomes, with only a 27% chance of survival to 12 months.From the qualitative studies, the fear of losing their baby was a predominant concern influencing both healthcare providers' and parents' experiences and perceptions in the NCU. Healthcare providers are the authority in the NCU; they focus solely on delivering lifesaving medical care and use mothers as assistants to achieve this goal. On the other hand, mothers manifested conditional trust in healthcare contingent upon improving their babies. The mothers were eager to participate in caregiving activities to improve the survival chances of their infants, which was the priority.Conclusions: This thesis shows that intrapartum-related adverse outcomes affect over 10% of births in Eastern Uganda, including stillbirths, early neonatal deaths, and IP-NE. Emergency referral and caesarean section had no impact on IP-NE risk. Severe IP-NE had the poorest outcomes, with only 27% surviving to one and a half years without disability. Moderate cases had better survival (87%), but only 67% were disability-free. Mild and healthy neonates had over 95% survival. Qualitative findings indicated that healthcare providers guide parental involvement in the NCU. The parents were willing to participate and comply with the rules, driven by their desperation for their babies' survival.List of scientific papersI. Wanduru P, Straneo M, Sadoo S, Tann C, Kakooza-Mwesige A, Rolland M, Hanson C. Prevalence, and risk of adverse intrapartum-related outcomes in Uganda: a cross-sectional study with nested case- control. [Submitted]II. Wanduru P, Straneo M, Sun S, Waiswa P, Kakooza-Mwesige A, Hanson. Infant Outcomes Following Intrapartum-Related Neonatal Encephalopathy in Eastern Central Uganda: A Cohort Study. [Manuscript]III. Wanduru P, Hanson C, Waiswa P, Kakooza-Mwesige A, Alvesson HM. Mothers' perceptions and experiences of caring for sick newborns in Newborn Care Units in public hospitals in Eastern Uganda: a qualitative study. Reprod Health. 2023;20(1):106. Epub 20230720.https://doi.org/10.1186/s12978-023-01649-1IV. Wanduru P, Hanson C, Kwesiga D, Kakooza-Mwesige A, Mölsted Alvesson H, Waiswa P. Parental participation in newborn care in the view of health care providers in Uganda: a qualitative study. Reproductive Health. 2024;21(1):155. https://doi.org/10.1186/s12978-024-01896-w